Challenges Facing Translating Arabic-TV news into English - Shaghati, Asst. Instr. Taha Yaseen (Manar Elsharq Journal for Literature and Language Studies, 2026)
This study examines the linguistic, cultural, and technical challenges of translating Arabic television news into English, a process that extends far beyond direct lexical substitution. Arabic news discourse, shaped by ideology, audience expectations, and sociopolitical context, presents complex constraints affecting both accuracy and reception. Structural differences between Arabic and English particularly in syntax, morphology, and rhetorical style complicate efforts to produce clear and idiomatically appropriate English texts. Arabic often employs high stylistic density, nominalization, and extended sentences, whereas English favors brevity, directness, and linear information flow, requiring translators to restructure content while preserving meaning. Cultural references add further difficulty. Arabic news frequently includes regional political terminology, historical allusions, and culturally embedded metaphors that may be unfamiliar to international audiences. Translators must decide whether to retain, adapt, or contextualize these elements, balancing clarity, neutrality, and audience understanding. Political sensitivity in Arabic media is pronounced, and translators must remain aware of potential ideological weight to avoid bias or misrepresentation. Technical constraints in television broadcasting intensify these challenges. Translators work under strict time pressure, often in live or near-live contexts, facing overlapping speech, regional dialects, and audiovisual synchronization requirements. Subtitles and voice-over formats impose spatial and temporal limits, forcing condensation without distortion. Specialized terminology in politics, economics, and military reporting further demands up-to-date knowledge and bilingual familiarity. The study concludes that translating Arabic TV news into English is a multidimensional task combining linguistic competence, cultural literacy, and technical expertise. Effective translation balances accuracy, accessibility, and ideological sensitivity while maintaining journalistic integrity. The research recommends enhanced translator training integrating media studies, political knowledge, and real-time translation skills, alongside closer collaboration between journalists and translators to ensure more reliable cross-linguistic news communication and a deeper understanding of Arabic-speaking societies in global media contexts.